Integrative transcriptomics unravels the central role of fatty acid elongation in early cotton fiber development - Xiaomei Ma; Gang Wang; Chengguang Dong; Feng Liu (PLoS ONE, 2026)
Cotton fiber initiation is a critical determinant of yield and quality. To decipher the genetic networks underlying this process, we conducted a time-series transcriptome analysis of a wild-type cotton (142-WT) and its fuzzless-lintless mutant (142- fl ) at 0, 1, and 2 days post-anthesis (DPA). Phenotypic characterization confirmed the absence of fiber protrusion in the mutant. Through integrated analysis of differentially expressed genes (DEGs) and weighted gene co-expression network analysis (WGCNA), we identified a key module highly correlated with fiber development. This module is overwhelmingly enriched for lipid metabolism pathways, notably fatty acid elongation. Furthermore, we identified 83 high-connectivity hub genes within this network, including key enzymes like 3-ketoacyl-CoA synthases ( KCS ) and regulatory transcription factors. Our findings propose a novel model in which the coordinated activation of fatty acid metabolism, particularly the biosynthesis of very-long-chain fatty acids, is essential for the initiation and early development of cotton fibers. This study provides crucial insights and valuable genetic resources for the molecular breeding of cotton with improved fiber traits.